Influence of grinding on the residual stress measurements of shot peened aluminum alloy AA7075 - Žagar, Sebastjan (Strojniški vestnik, 2019)
The present study aims to investigate the influence of grinding on shot peened (SP) aluminium alloy 7075 by means of residual stresses. The aluminium alloy was subjected to homogenization annealing at temperature 475°C for two hours and then followed by quenching in water to a room temperature. After that, the surface was shot peened with different Almen intensities and at different coverage to obtain compressive residual stresses in the surface layer of the material. Then the grinding operation is followed to reduce surface roughness and also to increase corrosion resistance. The first method used for measuring residual stresses was semi-destructive blind-hole drilling method and the second one was non-destructive X-Ray diffraction method. The resulting residual stress profiles reveals that residual stresses throughout the surface layer of all shot peened specimens are compressive nature. By comparing results of both methods it was shown, that after grinding the surface with small force (100N), the measured residual stresses at the grinding surface (XRD) are practically the same as measured by blind-hole drilling method at the same depth of 0,1 mm.
Keywords: AA7075; aluminijeve zlitine; aluminium alloy; blind-hole drilling; hrapavost; hrapavost površine; metoda z vrtanjem slepe izvrtine; microhardness; mikrotrdota; residual stresses; roughness; shot peening; udarno utrjevanje; X-ray diffraction; XRD metoda; zaostale napetosti